Therapeutic hypothermia as an adjunct to extracorporeal membrane oxygenation for acute respiratory distress and refractory hypoxemia. (July 2019) - Luc, Jessica G Y; Meyer, Steven R; Murtha, William J; Singh, Gurmeet
Legionella community–acquired pneumonia necessitating veno-venous extracorporeal membrane oxygenation for severe acute respiratory distress syndrome has been reported in adults. However, few options remain in cases of refractory hypoxemia on veno-venous extracorporeal membrane oxygenation. Herein, we describe adjunctive extended therapeutic hypothermia for refractory hypoxemia despite veno-venous extracorporeal membrane oxygenation for successful management of severe acute respiratory distress syndrome secondary to Legionella.